2019
DOI: 10.7150/thno.34493
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-338 Cluster activities on osteoblast differentiation: Potential Diagnostic and Therapeutic Targets for Postmenopausal Osteoporosis

Abstract: MicroRNAs (miRNAs) are the most abundant RNA species found in serum, and recently, several miRNAs have been found to be associated with osteoporosis. However, the development of such associated miRNAs into diagnostic and therapeutic targets remains unaddressed, mostly because of a lack of functional validation. Here, we identified circulating miR-338 associated with postmenopausal osteoporosis, and performed functional validation in vivo and in vitro . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 42 publications
2
54
0
Order By: Relevance
“…Osteoblast differentiation is a vital process for fracture healing, arising as a result of various intersecting factors [32]. We observed the upregulation of miR-5106 in exosomes isolated from M2 macrophages, and we found that this miRNA positively regulated osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 56%
“…Osteoblast differentiation is a vital process for fracture healing, arising as a result of various intersecting factors [32]. We observed the upregulation of miR-5106 in exosomes isolated from M2 macrophages, and we found that this miRNA positively regulated osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 56%
“…Lin et al conducted a very complex study to demonstrate that miR-338 clusters, including miR-338 and miR-3065-5p, inhibited osteogenic differentiation by osteogenic markers down-regulation [41]. Simulating an in vitro paracrine model by using continuous mouse bone cell lines, they showed that an miR-338 cluster was cross-transferred between OP-engaged and healthy OBs, reducing their bone deposition activity.…”
Section: Pm Op/ope Vs Pm Ctrsmentioning
confidence: 99%
“…Lin et al [ 66 ] analyzed the expression profile of miR-338 cluster (which includes miR-338-3p and miR-3065-5p), whose deregulation has been observed during in vitro osteoblast differentiation, in the serum of 15 OP patients compared with 15 HC, and also in an OP mouse model. An increase of the expression levels of miR-338 cluster members was observed both in sera of OP patients compared with HC and ovariectomized mouse, and ROC analysis confirmed their diagnostic potential in determining patients with or without osteoporosis.…”
Section: Circulating Mirnas As Potential Biomarkers In Bone Fragilmentioning
confidence: 99%